The Lacanian Concept of Cut in Light of Lacan's Interactions with Maud Mannoni - Razon, Laure; Putois, Olivier; Vanier, Alain (Frontiers in Psychology, 2017)
This article sets out to shed light on the Lacanian concept of cut (introduced in 1961-1962): it refers to the symbolic (i.e. linguistic) operation which produces the object a and thereby enables separation, through which the subject emerges. To that effect, we show how this concept benefitted from Lacan’s interactions with Maud Mannoni (1923-1998), who focused on clinical situations where implementing a cut in the subject’s environment is the only way to enable a separation between the child and the Other. Lacan first drew on Mannoni’s clinical elaborations about the retarded child’s alienation to the maternal fantasy: when the mother’s unconscious doesn’t leave room for the cut, it prevents the separation through which the child could become a subject. Lacan generalized this in the late 1960s: he broadened Mannoni’s alienation to the maternal fantasy to characterize a type of child symptom, where children become their mother’s non-separated, de-phallicized object a. Then, in the 1970s, Mannoni proposed an original theoretico-clinical setting to address the configurations where the object a isn’t separated: in the splintered institution, the team follows on projects of activities (professional, personal, etc.) outside the institution voiced by children who haven’t previously encountered the symbolic cut, by helping them realize these external projects. By thus acknowledging their attempts at establishing a cut and giving them consistency, the splintered institution helps them psychically elaborate separation.